The Impact of Positive Interpersonal Relationships on Performance and Productivity in the Workplace - Vindy Azzarah; Nadia Vita Nurul Aini; Syalma Ahzani; Nabila Sajidah Ghoziyah Wibowo (International Conference on Psychology and Education (ICPE), 2023)
The purpose of this study is to find out that the interpersonal relationships that are forged by employees in the workplace will have a positive impact on performance and productivity in the workplace. The research method used is using qualitative methods. qualitative method is a method that focuses on understanding the problems that exist in social life. Researchers use qualitative methods through literature study. From the results of the descriptive analysis, it was found that there was a significant and positive influence on interpersonal relations with the performance and productivity of human resources in the workplace. This means that if employees have good interpersonal relationships, it will have a positive impact on their work performance and productivity.